2018
DOI: 10.1128/mbio.01176-18
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Pleiotropy in the Bifunctional Surface Protein FadL (OmpP1) during Adaptation of Haemophilus influenzae to Chronic Lung Infection Associated with Chronic Obstructive Pulmonary Disease

Abstract: Nontypeable Haemophilus influenzae is an important pathogen in patients with chronic obstructive pulmonary disease (COPD). To elucidate the bacterial pathways undergoing in vivo evolutionary adaptation, we compared bacterial genomes collected over time from 13 COPD patients and identified recurrent genetic changes arising in independent bacterial lineages colonizing different patients. Besides finding changes in phase-variable genes, we found recurrent loss-of-function mutations in the ompP1 (fadL) gene. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 99 publications
(126 reference statements)
6
56
0
Order By: Relevance
“…The remaining SSR indels occurred in the haemoglobin-haptoglobin binding protein B-encoding gene hgpB, 316 which is involved in NP colonisation and iron acquisition (51), and lic3A, which encodes a 317 lipooligosaccharide (LOS) sialyltransferase that facilitates NTHi colonisation in different 318 anatomical sites (52,53). 319 Our genetic findings concur with the recent studies, which found that phase variation in lic3A, 320 hsdM3 and hgpB are common in NTHi isolates retrieved from COPD airways (17,46). In 321 addition to the hgpB SSR variant in 60068 BAL Hi1 that truncates the protein from 992 to 12 322 residues, a non-synonymous SNP (HgpBArg407Lys) was seen in 60295 BAL Hi1.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…The remaining SSR indels occurred in the haemoglobin-haptoglobin binding protein B-encoding gene hgpB, 316 which is involved in NP colonisation and iron acquisition (51), and lic3A, which encodes a 317 lipooligosaccharide (LOS) sialyltransferase that facilitates NTHi colonisation in different 318 anatomical sites (52,53). 319 Our genetic findings concur with the recent studies, which found that phase variation in lic3A, 320 hsdM3 and hgpB are common in NTHi isolates retrieved from COPD airways (17,46). In 321 addition to the hgpB SSR variant in 60068 BAL Hi1 that truncates the protein from 992 to 12 322 residues, a non-synonymous SNP (HgpBArg407Lys) was seen in 60295 BAL Hi1.…”
supporting
confidence: 82%
“…Previous studies have identified deleterious ompP1 mutations in ~33% of COPD 338 isolates, and in-frame ompP2 mutations (i.e. missense SNPs and indels) in ~20% of COPD 339 isolates (17,46). Similarly, we identified an in-frame ompP2 mutation in the 65001 BAL Hi1 340 isolate that occurred in the extracellular loop six motif (56) and increased OmpP2 length by 341 three amino acids.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…The three molecules reduced NTHi bacterial viability in a dose-dependent manner, quercetin being the one with the lowest MIC observed ( Figure 1B and Figure S1B). Genomic heterogeneity is a known feature for NTHi [44][45][46], which may lead to variable polyphenol susceptibility among strains, as is shown for other antimicrobials [33]. We evaluated the effect of quercetin, myricetin, and punicalagin on three NTHi clinical strains isolated from COPD sputum samples and belonging to different clonal types [45]; their viability decreased when exposed to polyphenols, with some MIC variations among them (Table S2).…”
Section: An Extract Of Cistus Salviifolius Rich In Polyphenols Has Anmentioning
confidence: 99%